The Influence of The Play Environment on Children's Learning Motivation - Wati, Dwi Agustina; Widyasari, Choiriyah (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to examine the impact of the play environment on student motivation at BA Aisyiyah II Banaran Kalijambe, Sragen. The research explores how the physical and social aspects of play-based learning influence students’ engagement and their learning outcomes.Methodology: A quantitative research design using a correlational approach was applied. Data was collected from 20 students at BA Aisyiyah II Banaran using a Likert scale questionnaire to measure their learning environment and motivation. Additional data was gathered through interviews with teachers, direct observation, and documentation analysis. The collected data were analyzed using descriptive statistics, correlation analysis, and linear regression to assess the relationship between the play environment and students’ motivation.Results: The findings indicate a moderate positive correlation (r = 0.67) between the quality of the play environment and student motivation. Further, regression analysis shows that improvements in the play environment significantly enhance student motivation (β = 0.875, p < 0.05). These results suggest that a well-structured play environment contributes to higher levels of motivation among students.Applications/Originality/Value: This research highlights the importance of both physical and social aspects of the play environment in enhancing student motivation. It provides practical insights for educators and policymakers to create more effective learning environments that support student engagement and achievement. The originality of this study lies in its focus on the integration of social interactions in play-based learning settings as a key factor in motivating students